Arih2 gene influences immune response and tissue development in chicken. Issue 10 (18th October 2019) - Wu, Guanxian; Xu, Sifan; Zhang, Wanting; Liu, Yang; Wang, Qiuyuan; Man, Chaolai
Abstract: Ariadne homolog 2 (ARIH2), as an E3 ubiquitin ligase, is one of the important factors involved in regulating biological functions, such as inflammation and skeletal muscle degeneration. In the present study, the full-length coding sequence of Arih2 gene was cloned from Hy-Line Brown chicken. The tissue transcriptional profiles of Arih2 gene at different developmental stages were detected using quantitative real-time PCR (qRT-PCR), and the Arih2 functional characteristics in immune response were analyzed. The results showed that the full-length coding sequence of Arih2 gene was 1473 bp, encoding 490 amino acids, and conservative between different species. The Arih2 gene was transcribed in various tissues at different developmental stages, and its transcriptional activities varied significantly between multiple tissues. With the development of chicken, Arih2 gene was basically up-regulated in heart, liver, kidney, skeletal muscle and glandular stomach, but fluctuated significantly in large intestine. In immune response, the transcriptional activities of Arih2 gene exhibited significant changes in the bursa, thymus and blood ( P <0.05). The results showed that Arih2 might be a multifunctional gene involved in tissue development and immune response in chicken, and have a potential possible application as diagnostic marker for identifying immune response.